Height-Age on the Risk of Delays in Toddler Development - Nurul Anjarwati; Wiwit Nurwidyaningtyas (Indonesian Journal of Global Health Research, 2026)
Short stature of toddlers is a height discrepancy according to age in toddlers which can cause interference with the development of fine movements, gross movements, speech and language as well as social independence. Short stature in toddlers can result in long-term deficits in physical and mental development so that they are unable to learn optimally at school compared to children of normal height. Short stature can be a normal or abnormal variant. Children with normal variations of short stature do not require treatment, while abnormal short stature in children needs to be recognized early. The aim of this study was to explore the impact of height discrepancy according to age on the risk of developmental delays in toddlers at the Children's Polyclinic at Panti Nirmala Hospital in Malang. This research design uses a cross-sectional method with a sampling technique carried out in this way, namely purposive sampling of 60 respondents, data collection is carried out by measuring the child's height and measuring development using the Denver test. Based on test Chi Square it can be seen that the value p = 0.000, this value is smaller than p <0.05, so the conclusion from this study is that there is a significant influence between the two variables where this result indicates short stature can increase the risk of delays in achieving the developmental stages of toddlers through validation of the DDST measuring instrument. This research can be input for nurses to do more aware, more agile and more improved knowledge regarding the development of management models for weight-age, height-age and nutritional status of children towards the achievement of toddler development stages.